Ketangguhan Petani Sawit dalam Upaya Pengelolaan Perkebunan Kelapa Sawit - Sawitri, Diah Panca; Rahmi, Tuti; Putra, Yanladila Yeltas (Indo-MathEdu Intellectuals Journal, 2025)
Palm oil plantations in Indonesia have experienced significant development in improving the country's economic growth and boosting the people's economy. Palm oil plantation crops are one of the plantations that have played an important role for the community in Merangin Regency. This study aims to describe how resilient palm oil farmers are in facing the problems of palm oil plantations in Merangin Regency. This research is qualitative research with a case study approach. Data collection from the research findings was carried out through observations and in-depth interviews with palm oil farmers in Pinang Merah Village and Rantau Panjang Village. Data analysis was conducted qualitatively through stages of data reduction, data presentation, and drawing conclusions. The analysis results revealed several indicators of resilience in oil palm management, including the commitment of oil palm farmers, the controls implemented, the challenges faced, and the impact of oil palm plantations on the lives of oil palm farmers.